A year in the city - Henderson, Kathy, 1949-; Howard, Paul, 1967- (Cambridge, Mass. : Candlewick Press, 1996)
A month-by-month description in pictures and words of what goes on in a city during the year.
Book Links (A.L.A.).
Elem. School Library Collection.
School Library Journal.
2.8
K-3
Keywords: City and town life -- Fiction; Seasons -- Fiction; Seasons -- Fiction